2022
DOI: 10.3389/fphys.2022.1024418
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plyometric training on skill and physical performance in healthy tennis players: A systematic review and meta-analysis

Abstract: Background: Plyometric training (PT) has been researched extensively in athletic populations. However, the effects of PT on tennis players are less clear.Methods: We aim to consolidate the existing research on the effects of PT on healthy tennis players’ skill and physical performance. On 30th May 2022, a comprehensive search of SCOPUS, PubMed, Web of Science, and SPORTDiscus (via EBSCOhost) databases was performed. PICOS was employed to define the inclusion criteria: 1) healthy tennis players; 2) a PT program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 106 publications
1
17
0
1
Order By: Relevance
“…Our meta-analysis revealed that agility performance was significantly improved after PT (ES = 0.96, moderate). This result aligns with findings from prior meta-analytic studies examining the impact of PT on agility among tennis [ 23 ], volleyball [ 25 ], and basketball players [ 17 ]. Enhancements in agility demand rapid force generation [ 70 ], and evidence indicates that PT may enhance the factor [ 71 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our meta-analysis revealed that agility performance was significantly improved after PT (ES = 0.96, moderate). This result aligns with findings from prior meta-analytic studies examining the impact of PT on agility among tennis [ 23 ], volleyball [ 25 ], and basketball players [ 17 ]. Enhancements in agility demand rapid force generation [ 70 ], and evidence indicates that PT may enhance the factor [ 71 ].…”
Section: Discussionsupporting
confidence: 88%
“…A great number of systematic reviews and meta-analyses have provided evidence for the efficacy of PT in enhancing physical fitness among athletes across various sports disciplines such as tennis [ 23 ], soccer [ 24 ], volleyball [ 25 ], handball [ 26 ], and basketball [ 17 ]. However, to our knowledge, no systematic review and meta-analysis have addressed the effects of PT on skill-related physical fitness in badminton players.…”
Section: Introductionmentioning
confidence: 99%
“…Fernández-Fernández et al asserts that NMT prior to regular tennis training proves effective in enhancing speed [ 26 ]. A meta-analysis corroborates the positive impact of PT on sprint speed for healthy tennis players [ 63 ]. In relation with the above results, the 20-m sprint ( p = 0.04; ES: 0.66) showed a significant improvement in the present study.…”
Section: Discussionmentioning
confidence: 77%
“…Meta-analyses were performed when a minimum of three studies provided sufficient data to calculate effect sizes (ES) ( Deng et al, 2022 ; Ramirez-Campillo et al, 2023 ). Mean and standard deviation data from pre- and post-intervention measures were used to compute effect sizes for performance outcomes in both the PT and control groups ( i.e ., Hedges’ g).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this meta-analysis aims to fill the gap by analyzing the distinct effects of PT compared to control conditions on various components of physical fitness that are relevant to racket sport athletes. Concerning prior meta-analyses ( Sole et al, 2021 ; Deng et al, 2022 ), we hypothesized that PT would yield greater effects than a control condition in enhancing the physical fitness of athletes involved in racket sports.…”
Section: Introductionmentioning
confidence: 99%